Legal Perspectives on Intellectual Property Rights Cases Related to Language Rhetoric in Trademark Registration - Gevan Naufal Wala (Greenation Research & Yayasan Global Resarch National, 2024)
This study analyzes the legal implications of Article 12 of the proposed Language Bill (RUU Bahasa) on trademark regulations in Indonesia, particularly its potential conflict with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The research employs a normative legal research methodology with an analytical and conceptual approach. The findings reveal that Article 12 of the Language Bill, which mandates the use of Indonesian language in trademarks, potentially violates existing trademark regulations, specifically Article 61 Paragraph (2) letter b of Law No. 15 of 2001. This requirement to change registered trademarks to Indonesian language could create legal uncertainty and adversely affect trademark owners' rights. Furthermore, the study indicates that such mandatory language requirements might negatively impact Indonesia's business and investment climate. The research concludes that harmonization between the Language Bill and existing trademark laws is crucial to maintain legal certainty and protect trademark owners' rights while supporting sustainable economic growth in Indonesia.